DEVELOPMENT OF OPPORTUNITY PIPELINE In Case Company ABB Oy, Transformers - Salo, Jaakko (My University, 2014)
The purpose of this study was to create an opportunity pipeline for ABB Oy, Transformer unit. The research problem of this study was that in the case company they did not have sufficient knowledge of sales opportunity projects in the markets and furthermore any system to manage them. The lack of sales opportunity awareness complicates quotation resource allocation but also hinders sales forecasting and decision making. The theoretical framework of this study, which consisted of sales process and knowledge management, gave the foundation to the empirical part. The empirical past consisted of introduction of the research methods and analysis of the findings. The research material was assembled by conducting semi-structured theme based interviews to key persons in internal and external units in ABB organisation. The discussed themes were based on the theoretical framework of this study. The interviews were analysed by qualitative methods and similarities were recognised among them. By the basis of the findings of the interviews, answers to the research question were defined. Tailored operations models were developed to instruct the opportunity pipeline activities and an internal strategy was created to support the opportunity pipeline operations in the Transformers unit. The developed operations models are instructions based on the suggestions and requirements of the interviewees and mainly directed to the area managers of the Transformers unit. The internal knowledge management strategy consisted of top management support, culture of organisational learning and measurement.
Keywords: Sales Process; Knowledge Management; Knowledge Management Strategy; Knowledge Sharing Barriers; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|